Prostituted Women and the British Empire. Issue 1 (June 2016) - Chatterjee, Ratnabali
In this article, the author has tried to historically trace the attempts of the colonial state to regulate and codify Indian women's sexual practices by segregating one section of women from their socio-cultural moorings. She has also tried to show how they were transformed from social beings into criminals through a negative act of commodification, as well as victims at a later stage. At the same time, the author takes into consideration the works of the British missionaries who, through their rehabilitation measures, provided a second voice in the colonial discourse.